2020
DOI: 10.3390/plants9060686
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Apparatus of Tabernaemontana ventricosa Hochst. ex A.DC. (Apocynaceae): Laticifer Identification, Characterization and Distribution

Abstract: Due to the inconsistencies in the interpretation of laticifers within the Apocynaceae, the current study aimed to distinguish, for the first time, the type and distribution of the laticifers in the embryos, seedlings and adult plants of Tabernaemontana ventricosa (Forest Toad tree). The characterization and distribution of laticifers were determined using light and electron microscopy. The findings revealed the presence of articulated anastomosing laticifers. The laticifers were found to have originated from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…Obtained results were in accordance to those found previously for other Asclepiadaceae [ 12 , 27 , 36 , 38 ]. While in other study, secretory cells were found towards leaf extremities [ 26 ].…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Obtained results were in accordance to those found previously for other Asclepiadaceae [ 12 , 27 , 36 , 38 ]. While in other study, secretory cells were found towards leaf extremities [ 26 ].…”
Section: Resultsmentioning
confidence: 83%
“…[ 37 ]. However, they can occur in the vascular tissue and cortical parenchyma in other species sections [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laticifers contain a complex solution including neutral lipids, acidic lipids, and phenolic compounds essential for the defense of plants against biotic and abiotic stresses (Naidoo, Naidoo, & Dewir, 2020; Pott, Osorio, & Vallarino, 2019). According to Vitarelli et al (2015), laticifers in the Crotoneae subtribe are the articulated type; they can be present in the subfamily Crotonoideae and constitute a plesiomorphic character for Euphorbiaceae.…”
Section: Discussionmentioning
confidence: 99%
“…The leaf segments were secured onto brass stubs with double-sided carbon conductive tape, and sputter-coated with gold for 3 min, using a Polaron SC500 Sputter Coater (Hemel Hempstead, London). A LEO 1450 scanning electron microscope at 5 kV was used to observe the leaf samples [ 19 ]…”
Section: Methodsmentioning
confidence: 99%